Constituency service in Turkey: a survey on MPs - Yasushi Hazama (European Journal of Turkish Studies)
This paper explores some causes and the consequences of constituency service in a proportional representational system. Turkey provides an interesting case here. First, its province-size constituencies generate a significant size of personal votes for a candidate, though nominated in the party list. Second, as in other non-western democracies, it is the service and allocational aspects of responsiveness that compose the most frequent demands from constituents to parliamentarians in Turkey. There exists, however, conflicting evidence regarding what priority Turkish parliamentarians give to constituency service. The analysis of the data collected through a questionnaire survey highlights several features of constituency service in Turkey. First, in terms of daily activities, parliamentarians spend for constituency service the largest part of their time at their own disposal. Second, for reelection purposes, parliamentarians consider their individual activities to be almost as important as party popularity. Third, the demand for and supply of constituency service depend on different politico-economic structures of the constituency. The smaller the constituency size, the larger will be the demand for and the supply of constituency service. The economically less developed constituencies tend to generate more demand than the more developed constituencies but do not significantly motivate the parliamentarians to provide constituency service. In addition, the Turkish parliamentarian’s turnover rate is much higher than in other democratic countries. Therefore even reelected parliamentarians have to take constituency service seriously. The statistical test shows no significant difference in the practices of constituency service between newly-elected and reelected parliamentarians.